2015
DOI: 10.1136/medethics-2015-102796
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining informed consent for genomics research in Africa: analysis of H3Africa consent documents

Abstract: BackgroundThe rise in genomic and biobanking research worldwide has led to the development of different informed consent models for use in such research. This study analyses consent documents used by investigators in the H3Africa (Human Heredity and Health in Africa) Consortium.MethodsA qualitative method for text analysis was used to analyse consent documents used in the collection of samples and data in H3Africa projects. Thematic domains included type of consent model, explanations of genetics/genomics, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…This is not surprising, as many of these ICDs were developed prior to the current guidelines, 19 and other studies have found similar results. 28 Yet, our research with GWAS investigators suggests that, although they believe results should be returned in some circumstances, the decision about whether to communicate them to participants is heavily influenced by what was written in the original ICD, and that investigators may view the ICD similar to a contract and feel bound to its terms. 29 RECs, likewise, are expected to ensure that return of results is consistent with the original ICD (https://gds.nih.gov/ 13faqs_gds.html).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as many of these ICDs were developed prior to the current guidelines, 19 and other studies have found similar results. 28 Yet, our research with GWAS investigators suggests that, although they believe results should be returned in some circumstances, the decision about whether to communicate them to participants is heavily influenced by what was written in the original ICD, and that investigators may view the ICD similar to a contract and feel bound to its terms. 29 RECs, likewise, are expected to ensure that return of results is consistent with the original ICD (https://gds.nih.gov/ 13faqs_gds.html).…”
Section: Discussionmentioning
confidence: 99%
“…Our protocols were included in an analysis of H3Africa Consortium consent documents [66] and we contributed to discussions on promoting fairness for genomic research in an African context [30]. …”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence from across the continent shows that the majority of research participants do not grasp these concepts of genomics or are unable to explain what they mean , although there is notable variation with regards to the location (urban/rural) and demographics of research participants (Marshall et al 2014). There is often difficulty in finding local equivalent words for genomics terms and explaining these novel, unfamiliar and highly technical subjects in local languages (Munung et al 2016;Traore et al 2015;Tindana et al 2012). The process of working out comprehensible language is crucial, whether in writing or verbally.…”
Section: Protection Of Participantsmentioning
confidence: 99%
“…Unsurprisingly, there is no uniform informed consent template across different countries for genomic studies because there are wide cultural and ethnic disparities that make broad consent for data sharing difficult to apply across multinational studies (Wright et al 2014). There are legal and ethical challenges to the transition from narrow consent, which is the usual practice, to broad consent, which is necessary in emerging fields, such as genomics research (Munung et al 2016;Tindana et al 2014;De Vries et al 2015c). There are additional layers of bureaucratic obstacles in some countries, due to the strict requirements for Materials Transfer Agreements (MTAs).…”
Section: Guidelines and Requirements Of Different Ethics Boardsmentioning
confidence: 99%
See 1 more Smart Citation